2019
DOI: 10.1111/aos.14043
|View full text |Cite
|
Sign up to set email alerts
|

Retinal oxygen saturation in 1461 healthy children aged 7–19 and its associated factors

Abstract: Purpose The aim of the present study was to investigate age‐specific normative retinal oxygen saturation values and explore the associated factors in healthy Chinese school‐aged children with different refractive statuses. Design Population‐based observational cross‐sectional study. Methods Children aged 7–19 years were enrolled. Each participant underwent a series of comprehensive ocular examinations, including axial length (AL), cycloplegic refraction and Oxymap T1 imagery following cycloplegia. The acquired… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…These studies had inconsistent findings regarding the association between retinal arteriolar oxygen saturation and myopia. Our findings of lower retinal arteriolar oxygen saturation in myopia were similar to Zheng et al17 and Chen et al24 The studies by Liu et al18,25 in younger populations, however, both found contrasting trends of higher arteriolar saturation with more myopic refraction and longer AL. One of the key factors affecting the relationship, thus, appears to be age, with studies in adult populations, including our current study, finding lower arteriolar saturation with myopia, and studies in children finding the opposite.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These studies had inconsistent findings regarding the association between retinal arteriolar oxygen saturation and myopia. Our findings of lower retinal arteriolar oxygen saturation in myopia were similar to Zheng et al17 and Chen et al24 The studies by Liu et al18,25 in younger populations, however, both found contrasting trends of higher arteriolar saturation with more myopic refraction and longer AL. One of the key factors affecting the relationship, thus, appears to be age, with studies in adult populations, including our current study, finding lower arteriolar saturation with myopia, and studies in children finding the opposite.…”
Section: Discussionsupporting
confidence: 90%
“…However, in another cross-sectional study aiming to provide normative data for retinal vessel oxygen saturation levels in 122 young Chinese subjects aged 5 to 18 years with mean refractive error of −3.25 ± 2.49 D (range, −8.88 to +3.13),18 higher retinal arteriolar oxygen saturation levels correlated with more myopic SE. Liu et al25 reported the normative retinal oxygen saturation values in 1461 Chinese children aged 7 to 19 years and found that longer AL was associated with higher arteriolar saturation and AVD. A cross-sectional study by Yang et al20 included subjects aged 19 to 30 and found no significant difference in retinal blood saturation between the group with refractive error less than −3.00 D and the other with refractive error of −3.00 D and above.…”
Section: Discussionmentioning
confidence: 99%
“…But this compensatory effect disappears immediately when HM occurs, making the retina more prone to pathological changes. Meanwhile, Liu [14] found that the choroid is involved in the transmission of biological signals from retina to sclera, and is involved in the regulation of scleral remodeling and staphyloma. Therefore, more attention should be paid to choroid to assess the progression of PM.…”
Section: Discussionmentioning
confidence: 99%
“…67 VO2 was lower in females than males, on which conflicting evidence exists, and could reflect the lower systemic basal metabolic rate. 47,68 Smoking was also associated with reduced VO2 and could be related to the reported reduced O2 uptake present in other systems. Lastly, although the average, resting OEF was consistent with previous reports, we found that it was lower in smokers.…”
Section: Oxygen Extraction (Vo2)mentioning
confidence: 90%